A Case Study: Quantitative Evaluation of C-Based High-Level Synthesis Systems. (6th July 2008) - Hammami, Omar; Wang, Zhoukun; Fresse, Virginie; Houzet, Dominique
Abstract : Embedded systems require a high-level abstraction modeling to tackle their complexity and improve design productivity. C-based design techniques and methodologies have been proposed for this purpose. Various IPs with diverse complexities and functionalities can be selected to build a system. However, area and energy issues are paramount in this selection process. Implementation hints should therefore be available at the highest possible level of abstraction. Some C-based tools have been proposed in this order through either true synthesis or estimation. In this paper, we conduct through a case study an evaluation of C-based design of embedded systems and point out the impact of behavioral synthesis on embedded systems multiobjective high-level partitioning.